2022
DOI: 10.1177/17585732221090821
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic debridement for acute hemorrhagic subacromial bursitis following COVID-19 vaccine administration: A case report

Abstract: The rapid rollout of vaccinations in response to the COVID-19 pandemic has led to their widespread distribution and administration throughout the world. The benefit of these vaccinations in preventing the spread of the disease and diminishing symptoms in patients who contract COVID-19 has been fervently studied and reported. While vaccinations remain an effective and generally safe method of limiting disease transmission and virus-related mortality, vaccine administration is not completely without risk. Should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For subgroup purposes, that patient is counted in the cases from the literature [9] . In total, 28 patients were included from literature [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For subgroup purposes, that patient is counted in the cases from the literature [9] . In total, 28 patients were included from literature [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has shown that up to 22% of cases ultimately require surgery [5] . At the time of reporting, only 2 patients in the subgroup analysis had undergone surgery, one for septic arthritis and the other for hemorrhagic bursitis [9] , [14] . No VAERS cases had undergone surgery at the time of reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Although the patient eventually experienced complete resolution of the bursitis, the unnecessary antibiotic exposure raised concerns about the development of antibiotic resistance. Another case reported by Mayer et al (12) involved subacromial bursitis as a complication following a COVID-19 vaccine administration at a too-high location. The patient experienced acute severe pain, disrupted daily activities, and lowgrade fever.…”
Section: Discussionmentioning
confidence: 97%
“…She had attained full range of motion 4 weeks after the surgery. 8 7 26 Male Moderna mRNA COVID-19 vaccination First Twenty-four hours after receiving vaccination Wrong injection site There is slight swelling on the right shoulder, and there is a vaccine injection site on the outer edge of the shoulder peak. Severe pain during shoulder joint activity, limited forward and lateral rotation movement White blood cells count of 7500/uL (normal), erythrocyte sedimentation rate of 5.0 mm/hr (normal), and C-reactive protein of 1.2 mg/dL (elevated).…”
Section: Methodsmentioning
confidence: 99%